Analysis of the Application of the Ultimum Remedium Principle in the Legal Process of Juvenile Offenders - Lumbantoruan, Abram Andriano Samapta; Anggusti, Martono; Sihotang, Lesson (Indonesian Journal of Law and Justice, 2025)
The application of the principle of ultimum remedy under the legal age of children who commit crimes is an effort to protect the health of children and ensure a more humane approach in the criminal system. This shows that after alternative forms of education, such as diversification and restorative justice, have been discussed, child care or education should be the last option. The purpose of this study is to analyze the mechanisms underlying the application of as ultimum remedy as well as the legal procedures applied to children who deviate and act like criminals. The method used in this study is normative juridical regarding laws, cases, and conceptual. The results of the study indicate that the implementation of as ultimum remedy still faces many challenges, such as a lack of understanding of the legal system, lack of rehabilitation facilities, and lack of attention to diversion of implementation. In addition, older children have a higher sensitivity to criminal acts, therefore a more comprehensive approach is needed in handling them. The principle of ultimum remedy can be integrated into child protection practices by complying with a set of rules that encourage cooperative conflict resolution. This study recommends training of law enforcement officers, improving rehabilitation facilities, and integrating legal education to create a more humane child protection system that focuses on child safety.